مزاح کے انسانی نفسیات پر اثرات اسلامی تعلیمات کی روشنی میں: Effects of humor on human psychology in the light of Islamic teachings - Hussain, Wasif (Al-Amīr Research Journal for Islamic Studies, 2022)
Every branch of art leaves a deep impact on the human psyche, but the immortal fact is that the reason for their creation is also to reduce the tension of the human mind. The most representative theory of humor in philosophy and psychology and even in physics. Is the idea of ​​well-being, comfort or well-being? Broadly speaking, this suggests that humor (which has an obvious physiological effect) has effects on the nervous system and allows different levels of stress to be released. In other words, laughter and good humor have the ability to release stored nervous energy. Humor is included in human nature and man has a strong desire for this thing that there should be such means for him to express joy and expansion. Because through them, man is blessed with mental and physical peace and comfort. In these things, he considers the survival of his self-respect. Islam not only allows humor, sports and entertainment, but also sets rules and regulations within which human beings can fulfill their natural needs. Its cultural traditions should also be propagated. As the head and governor of the Islamic state, the Holy Prophet (ﷺ) made the best arrangements for his state, the taste of the people and their entertainment, and set an example for the rulers that, like other matters, oppression in this not to be taken for granted, fun and humor are part of human nature. He (ﷺ) allowed fun and laughter and He (ﷺ) himself used to be cheerful. Islam admires cheerfulness and cheerfulness, and encourages it so that people can be refreshed and perform their duties in an auspicious manner. Through this paper, it will be clarified that what are the effects of humor on human psychology and what are the teachings of Islam and the Prophet of Islam in this regard. Key Word: Fine Arts, Humor, Human terms, Human humor